FOTODEGRADASI METILEN BIRU DENGAN SINAR ULTRAVIOLET DAN KATALIS ZnO - Diantariani, Ni Putu; Widihati, Ida Ayu Gede; Ratih Megasari, I G. A. A. (Jurnal Kimia (Journal of Chemistry); Vol. 8, No. 1 Januari 2014DO - 10.24843/JCHEM.2014.v08.i01.p21, 2014)
Study on  photodegradation methylene blue with ultra violet light and catalyst ZnO has been carried out. This study include determination of quantity of catalyst ZnO optimum  with radiation and without radiation, the optimum of pH, the optimum UV light radiation time, and the effectivity of photodegradation at optimum condition. The results of the research showed that percentage of degradation highly influence by the quantity of catalyst, pH of the methylene blue solution, and time of ultra violet radiation.  In this study, quantity of catalyst ZnO optimum of degradation methylene blue with UV light radiation was 40 mg, whereas degradation methylene blue without UV light radiation was 50 mg. The optimum pH of fotodegradation methylene blue occurs at pH 12 and the optimum UV light radiation time was 5 hours.  The effectivity photodegradation methylene blue at optimum condition was (94,67 ± 0,35) %.
Keywords: Photodegradation, Methylene Blue, Catalyst ZnO